MENINGKATKAN MUTU LEMBAGA PENDIDIKAN DENGAN PRINSIP-PRINSIP CROSBY: PENERAPAN UNTUK KEUNGGULAN PENDIDIKAN - Lutfi Firdausi; Akhyak Akhyak; Nur Efendi; As’aril Muhajir (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2023)
The application of Crosby's principles in improving the quality of educational institutions is very important considering the quality of education is a major factor in creating quality human resources and able to compete in the current era of globalization. The Zero Defect concept introduced by Crosby can be applied in educational institutions to improve the quality of learning, create a safe and comfortable learning environment, and increase customer satisfaction, namely students and parents. The type of research used is library research. Literature study is a research method carried out by collecting and analyzing data or information derived from written sources such as books, journals, papers, articles, and other documents. The type of research used is library research. Literature study is a research method carried out by collecting and analyzing data or information derived from written sources such as books, journals, papers, articles, and other documents. In applying the Crosby principles, educational institutions should focus on preventing errors or defects at an early stage, by ensuring that the learning process is carried out properly and correctly. Educational institutions must also ensure that all components of education, such as teachers, curriculum, learning methods, and facilities, meet the quality standards that have been set. In addition, the role of management in leading and improving the learning process is also very important to achieve Zero Defect quality.